The STAKEHOLDERS’ LEVEL OF AWARENESS AND ATTAINABILITY OF CAGAYAN STATE UNIVERSITY VISION AND MISSION AND GRADUATE SCHOOL GOALS AND OBJECTIVES: STAKEHOLDERS’ LEVEL OF AWARENESS AND ATTAINABILITY OF CAGAYAN STATE UNIVERSITY VISION AND MISSION AND GRADUATE SCHOOL GOALS AND OBJECTIVES - Talosa, Arlene; Licopit, Diana Grace; Macadangdang, Kimberly; Utanes, Nargloric; Cabalbag, Antonio (International Journal of Arts, Sciences and Education, 2021)
Using descriptive research design, this study aimed to assess the stakeholders’ level of awareness and the attainability of the Cagayan State University vision and mission and the Graduate School goals and objectives. Data were collected using researcher-made questionnaires from 128 respondents consisting of faculty members, alumni, students and school clienteles/heads. Findings reveal that the stakeholders were very much aware of the CSU vision and mission, the Graduate School goals and the program objectives of PhD-Educational Management and MAEd-Educational Management while much aware of the program objectives of MAEd-English, MS Teaching Mathematics and MS Information Technology. On attainability of the CSU VMGOs, the stakeholders perceived that the Graduate School serves to a very great extent its purpose towards employment and/or promotion, research and development capability, professional development, furthering of studies and developing expertise among its students and graduates. Intensifying dissemination strategies, curriculum input for research capability for students and further research were highly recommended.